Managing incompatibility of economic growth and environmental preservation through environmental impact assessment in Malaysia: the case of river water pollution - Eissa, Garoot Suleiman (International Journal of Science Commerce and Humanities, 2014)
This study is devoted to the assessment of the influence of Environmental Impact assessment (EIA), as a tool of environmental management in Malaysia, on environmental preservation and sustainable development. It is important to realize that achievement of rapid rates of economic growth and environmental preservation are inherently incompatible goals because economic development is the source of environmental degradation. However, EIA is a preemptive measure carried out during the planning of development projects aimed at enhancing simultaneous achievement of both goals. Its purpose is to block implementation of potentially polluting development activities. In Malaysia all important development projects are subjected to EIA to some degree. But, there are claims and counter claims in the literature that one goal is sacrificed for the sake of the other. Two procedures are adopted: 19 development activities are targeted for detailed evaluation by the headquarters of the Department of the environment (DOE); while otheractivities are either subjected to preliminary assessment by offices of the DOE at the local level or in some cases no assessment is considered necessary.In the present study projects subjected to either detailed or preliminary assessment will be held as independent variables. Whereas, river water pollution indicators as well as the flow of foreign direct investment and total annual investment are designated as dependent variables and hypotheses about relationships were tested. The method of assessment features the use of Spearman’s rho to examine association. A substantial part of the study, however, takes the form of a description of EIA administrative procedures. Policy implications will be pointed out. Results of the study suggest that at least as far as river water is concerned more emphasis was placed on economic growth to the detriment of environmental preservation. Key Words: environmental impact assessment, water pollution, environmental management, investment, FDI, DOE INTODUCTION The significance of environmental policies and management can hardly be overstated in light of the current Earth warming and other spectacular environmental events. Some are beginning to recall the doomsday predictions and conjectures made by the Club of Rome back in the 1970s (Meadows, et. al, 1972.). It is important to underscore that such speculations drew attention to the potential incompatibility between sustained 1The research